Analysis of consumer protection system in improving expedition services from an Islamic perspective: A case study of insurance at J&T Express Medan - Fadillatunnisa, Fadillatunnisa; Nasution, Muhammad Lathief Ilhamy; Nasution, Juliana (Journal of Islamic Economics Lariba, 2024)
IntroductionAs the economic landscape in Indonesia continues to evolve, there is a growing demand for shipping services. Nevertheless, from an Islamic perspective, research regarding insurance protection for shipped goods remains limited.ObjectivesThis research aims to examine consumer protection in enhancing expedition services for the shipment of goods at J&T Express Medan, focusing on the forms of protection against delays, damages, and losses during delivery due to negligence in the shipment process, which results in losses for consumers.MethodThe research methodology employed is qualitative research with a descriptive approach. This study utilized both primary and secondary data.ResultsIn the context of J&T Express's regular services, the service provider includes protections such as insurance and wooden packaging if deemed necessary by consumers to prevent damages and resultant losses during the shipment of goods. To ensure the safety of shipped items, J&T always offers insurance options for every item dispatched, especially for high-value items. Additionally, J&T Express provides packing services to guarantee the security and safety of the transported goods.ImplicationsThis research provided insights for sellers on whether they should opt for insurance protection or not based on the nature, fragility, and value of the items being shipped.Originality/NoveltyThis study contributes to insurance protection in the context of shipments from an Islamic perspective in Indonesia.